Islamic School and Arab Association: Aḥmad Sūrkatī’s Reformist Thought and Its Influence on the Educational Activities of al-Irshād - Motoki Yamaguchi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
Al-Irshād is an organization formed by the Arabs in present-day Indonesia in 1914, which advocates Islamic reform. This article examines its educational activities in the Dutch colonial period, elucidating the thoughts of its founder and leader, Aḥmad Sūrkatī, and the process of the integration of Arabs into the host society. Sūrkatī’s thought is distinguished from other Arab reformists for its emphasis on “egalitarianism” and its lack of a tendency towards Arab nationalism. From early on, he attempted to adapt the al-Irshād schools to the colonial education system in order to attract indigenous (pribumi) students, as well. In the late 1920s, he began to be locally oriented, with a focus territorially limited to Indonesia. The educational activities of al-Irshād in the 1930s also indicated the weakning of Ḥaḍramī/Arab-orientation. By the late 1930s, the opinion of al-Irshād was decisively inclined toward integration within the host society.DOI: 10.15408/sdi.v23i3.3268